Cupriavidus metallidurans CH34, a historical perspective on its discovery, characterization and metal resistance. Issue 2 (3rd December 2020) - Mergeay, Max; Van Houdt, Rob
ABSTRACT: Cupriavidus metallidurans, and in particular type strain CH34, became a model bacterium to study bacterial resistance to metals. Although nowadays the routine use of a wide variety of omics and molecular techniques allow refining, deepening and expanding our knowledge on adaptation and resistance to metals, these were not available at the onset of C. metallidurans research starting from its isolation in 1976. This minireview describes the early research and legacy tools used to study its metal resistance determinants, characteristic megaplasmids, ecological niches and environmental applications. Abstract : This minireview describes the isolation, early research and legacy tools used to study Cupriavidus metallidurans CH34, a model organism for bacterial metal resistance.